Applied Laplace transforms and z-transforms for scientists and engineers a computational approach using a mathematica package - Graf Urs (Basel Birkhauser Verlag, 2004)
The book presents theory and applications of Laplace and z-transforms together with a Mathematica package developed by the author. The package substantially enhances the built-in Laplace and z-transforms facilities of Mathematica. The emphasis lies on th
Accompanies a CD-ROM bearing acc no D653
Keywords: Laplace transforms; Transforms(Integral operators); Z-transforms